Construction and Characterization of a Diphase Two-Dimensional Halogen-Bonded Organic Framework Based on a Pyrene Derivative - Gong, Guanfei; Xie, Fei; Wang, Lu; Wang, Jike; Chen, Shigui (Synlett, 2022)
Crystalline porous materials have received extensive attention due to their fascinating structures and wide range of applications. We report a novel diphase two-dimensional (2D) halogen-bonded organic framework (XOF-TPP) based on 1,3,6,8-tetra(pyridin-4-yl)pyrene (TPP). XOF-TPP was constructed through [N···I+···N] interactions between the pyridyl groups of TPP and iodonium cations. The formation of XOF-TPP was monitored by X-ray photoelectron spectroscopy, IR spectroscopy, powder X-ray diffraction, scanning electron microscopy, and high-resolution transmission electron microscopy, and simulated theoretically. Small-angle X-ray scattering indicated that the XOF-TPP exists as a 2D periodic structure. This diphase 2D halogen-bonded organic framework has promise for practical applications in supramolecular functional materials.
Keywords: crystalline porous materials; organic frameworks; tetrapyridinylpyrene; halogen bonding